Corporate social responsibility training : exploring the antecedents to corporate social entrepreneurship - Jackson, Chad Allan (Kansas State University, 2014)
Leaders of organizations are becoming more aware of their company’s potential adverse impact on society and are facing added pressure from stakeholders to find ways to mitigate this impact (Lancey, Cooper, Hayward, & Neuberger, 2010). The field of adult education, through its history in human resource development and social responsibility, can directly influence an organization’s corporate social responsibility strategy and thus its impact on society (Garavan, Heraty, Rock, & Dalton, 2010). This study aims to provide insight into the relationship between socially conscious human resource development training programs and the recommendation of new corporate social responsibility ideas for the organization. Furthermore, as many organizations are increasingly using entrepreneurial approaches to enhance their corporate social responsibility strategies (Austin, Leonard, Reficco, & Wei-Skiller, 2006), this study explores the relationship between entrepreneurial and social organizational antecedents perceived by 152 company managers and the development of new corporate social responsibility ideas for the organization. This research utilizes exploratory factor analysis and multiple regression to analyze the results of an online survey. The results of the analysis indicated that a statistically significant relationship existed between the number of socially conscious human resource development training programs attended and the recommendation of new corporate social responsibility ideas. Additionally, this research indicated that a manager’s perception of the level of social proactiveness in a firm is a significant organizational antecedent that correlates with the recommendation of new corporate social responsibility ideas.
Keywords: Corporate Social Responsibility; Human Resource Development; Corporate Entrepreneurship; Adult Education (0516); Entrepreneurship (0429)